The Right of the Head of State to Veto Bills : A Comparative Study - Salem, Mustafa (Journal of Legal Sciences, 2023)
The legislative authority's approval of a project is not enough, as the state president's approval is crucial. If the president doesn’t approve the project within the period determined by the constitutions, it shall be returned to the parliament for further discussion and voting, Either by an ordinary or strict majority, according to the provisions of the constitutions of the countries. To explain the right of objection, we explained, in the First Topic, the definition and distinction, and we explained, in the Second Topic, the legal nature of the right of objection, its kinds, and its constitutional base. In the Third Topic, we discussed the conditions of the right of objection, its procedures, and its effects. Then, the conclusion that included the most important result is that the objection to laws projects is limited to the state president of the Federal Supreme Council and the state president in Egypt. , while it is not stipulated in the Iraqi Constitution, and that the objection to the laws projects didn’t have any reference to the reason behind objection or majority required for the second reading, and the recommendation regarding the suggestion of a constitutional amendment that organizes the objection right in a more detailed way and in a certain period